Endorsement as a Marketing Strategy Trend in Islamic Perspective - Ahmad Ali Sopian (Islamicate Institute, 2020)
The endorsement is an activity where business owners endorse or ask celebrities to give testimonials and promote their homework through social media. The effectiveness of endorsements lately is considered as a marketing strategy that is widely relied on by business people, especially the sale of products that use the means of purchase and payment with the online system. The methodology used in this paper is the study of literature, where the collection of reference sources is based on the publication of scientific works and unpublished papers. The conclusion of the results of this study is endorsement is considered as an effective social media promotion where actors or figure figures obtain products for free from producers with the obligation to do testimonials and conduct product promotions. In the review of the effectiveness of Islam Endorsement falls into the scope of the case mu'amalah al-adat which means the original law of the case is allowed as long as it does not contain prohibited elements in shari'a that can change the law to be prohibited.